HUBUNGAN PENGETAHUAN TENTANG CORONAVIRUS DISEASE 2019 DENGAN TINGKAT KEPATUHAN MELAKUKAN 3M (MEMAKAI MASKER, MENCUCI TANGAN, DAN MENJAGA JARAK) PADA MAYARAKAT DI PASAR BARU LANGOAN - Nicita Aprilia Rau; Septriani Renteng; Valen Fridolin Simak (Universitas Sam Ratulangi, 2022)
Background: COVID-19 is part of a family of viruses that cause illnesses ranging from the flu to more severe illnesses such as MERS-CoV and SARS-CoV. The virus will spread even more if people don't implement 3M. One of the things that is needed to improve compliance related to 3M is to have good knowledge regarding COVID-19. Objective: This research aims to determine the relationship between knowledge about corona virus disease 2019 with the level of compliance with 3M (wearing masks, washing hands, and maintaining distance) in Pasar Baru Langoan. Methods: This research method is a quantitative research method and the sample in this study amounted to 92 respondents with a sampling technique is purposive sampling. The instrument used with the knowledge questionnaire about COVID-19 andÂ the Compliance questionnaire wearing masks, washing hands, and maintaining distance with the results of the validity and reability test results obtained r count > r table and Cronbach alpha value > 0,6 . Results: Based on the results of the study, it shows that there is a relationship between knowledge about corona virus disease 2019 with the level of compliance with 3M (wearing masks, washing hands, and maintaining distance) with p-value = 0.000. Conclusion: It can be concluded that knowledge about corona virus disease 2019 is related to the level of compliance with 3M (wearing masks, washing hands and maintaining distance) at Pasar Baru Langoan.Keywords: Knowledge; Compliance; COVID-19.